Efficient and Anisotropic Second Harmonic Generation in Few‐Layer SnS Film. Issue 22 (2nd September 2021) - Zhu, Menglong; Zhong, Mianzeng; Guo, Xiao; Wang, Yongsong; Chen, Zhihui; Huang, Han; He, Jun; Su, Chenliang; Loh, Kian Ping
Abstract: Group‐IV monochalcogenide ferroelectric materials possess fascinating nonlinear optical properties and electro‐optical effects which play a vital role in 2D ferroelectrics, multiferroics and nonlinear optoelectronics. However, the studies of nonlinear optical properties of group‐IV monochalcogenides are still in their infancy stage. Herein, the preparation of few‐layer SnS by the molecular beam epitaxy (MBE) method is reported and the efficient second harmonic generation (SHG) of SnS monochalcogenide is systematically scrutinized by using ultrafast nonlinear optical spectroscopy. The obtained thickness‐dependent SHG is highly related with the coherence length. Second‐order nonlinear susceptibility of few‐layer SnS is also obtained. Polarization‐dependent SHG studies reveal its intrinsic anisotropy pattern and can be utilized to identify the crystalline orientation of few‐layer SnS film. Abstract : High quality few‐layer SnS is successfully prepared by molecular beam epitaxy. Efficient second harmonic generation (SHG) of the few‐layer SnS is systematically investigated. SHG anisotropy study is applied to determine the crystalline orientation of group‐IV monochalcogenides.